Fatty acid composition of coffee oil: comparison of methyl esters preparation - Gutierrez, L. E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
Green bean coffee (Coffea arábica L., cv. Mundo Novo) was treated with petroleum and oil was analised in relation to fatty acid composition. Three methods of esterification were used and the results statistically analised. Significant differences were not observed between methods of LUDDY et alii (1960) and A.O.A.C. (1965). The method with previous saponification showed significant difference only to linoleic acid when was compared with A.O.A.C. method.